On the Relevance of Geodetic Deformation Rates to Earthquake Potential. Issue 11 (5th June 2021) - Wang, Kelin; Zhu, Yijie; Nissen, Edwin; Shen, Zheng‐Kang
Abstract: Despite the importance of viscoelasticity in the evolution of crustal stress/strain being widely recognized, the interpretation of interseismic geodetic measurements for assessing earthquake potential is still based overwhelmingly on elastic models. The reasons for this disparity include conflating deformation rates with deformation itself and the lack of a succinct representation of the seismic readiness of a locked fault in a viscoelastic Earth. Using a classical viscoelastic model for strike‐slip faults, we reiterate the commonly overlooked message that, if the recurrence interval is long, most of the strain energy for the next earthquake accrues early in the cycle, and low strain rates later in the cycle by no means indicate diminished rupture potential. Fault stress stays near failure for much of the late interseismic period which may explain why slow slip‐rate faults have more variable recurrence intervals than fast slip‐rate faults. We propose to use displacement deficit instead of slip deficit to represent seismic readiness. Plain Language Summary: Modern satellite measurements can reveal how quickly faults are being loaded by tectonic plate motions, and seismic hazard models use these loading rates as proxy for the likelihood of a pending earthquake. However, because of the partially fluid‐like behavior of Earth's interior, these loading rates have actually evolved with time since the last rupture. For faults with long intervals between successive earthquakes, these rates slow down substantially as the next event draws near. We, therefore, caution that slow rates of loading should not be assumed to reflect limited earthquake potential. Key Points: Because of viscoelasticity, faults with long recurrence intervals accrue most of their elastic strain early in the interseismic period Strain rates should not be conflated with stored strain, and slow geodetic deformation rates do not imply limited earthquake potential For strike‐slip faults, "Relative Displacement Deficit" is a better measure of the earthquake readiness of a fault than "slip deficit"